Interleukin-6 promoter polymorphisms (-174 G/C) in Malaysian patients with systemic lupus erythematosus. - Chua, K.H.; Kee, B.P.; Tan, S.Y.; Lian, L.H. (Associação Brasileira de Divulgação Científica, 2009)
Systemic lupus erythematosus (SLE) is a chronic autoimmune disease that involves the inflammation of various organs upon deposition of immune complexes and is characterized by uncontrolled B cell hyperactivity. Despite intensive research on the etiology of the disease, the exact cause of the onset of SLE is unknown. The pathogenesis of the disease has been proposed to be associated with the imbalance of T helper type 1 (Th1) and Th2 cytokine activities. Elevated serum levels of interleukin-6 (IL-6), a Th2 cytokine with various functions in the regulation of human biological systems, are observed in SLE patients. In the present study, 100 Malaysian SLE patients and 100 controls were evaluated in order to determine the association of polymorphisms existing in the promoter region of the IL-6 gene with the onset of SLE. The homozygous G genotype was found to be significant in SLE patients (chi(2) = 33.754; P = 0.00000000625), whereas the heterozygous G/C genotype was significant in the controls (chi(2)= 25.087; P = 0.000000548). We suggest that the C allele might have a masking effect on the G allele when both alleles are present in heterozygous individuals. However, we did not observe any significant association of the homozygous C allele with the onset of SLE or with protection from the disease (chi(2) = 1.684; P = 0.194366).